A critical reflection on accessing women with learning disabilities to participate in research about sensitive subjects through organisational partnerships. - Earle, Sarah; Ledger, Sue; Tilley, Elizabeth; Walmsley, Jan; Chapman, Rohhss; Townson, Lou (British Journal of Learning Disabilities, 2020)
Accessible summary: This article is about reaching out to people with learning disabilities to participate in research on sensitive topics, like contraception. Contraception is a way to prevent pregnancy.The article shows that working with organisations can help to find and support people with learning disabilities to take part in research.The article explores what research teams need to do when working with organisations to find and support research participants. Background: Contraceptive use by women with learning disabilities differs from that of nondisabled women of a similar age. Women with learning disabilities start contraception earlier and often use it when they are not sexually active. Hence, there is a need to hear directly from these women about their experiences of contraceptive decision‐making. However, accessing women to discuss a sensitive topic such as contraception poses significant challenges to researchers. Materials and Methods: The study was qualitative in nature and involved conducting semi‐structured interviews with 19 women. This paper reports on the methodological challenges and findings from the project which have wider implications for research on sensitive topics with hard‐to‐reach groups. It reflects critically on the challenges of accessing women with learning disabilities to participate in research on contraception. Results: Twelve of the 19 participants in our project were recruited through two organisations. Working in partnership with organisations that had a keen interest in the research and endorsed it at senior level enabled us to overcome recruitment challenges. However, working in this way raised gatekeeping issues that impacted upon data collection and may have affected our substantive findings. Conclusions: Working in partnership with organisations can be an effective and practical way of recruiting participants that researchers may otherwise find hard to reach. However, organisational partnerships can be hard to develop and take time. We argue that it is important to reflect openly and honestly about the methodological and ethical issues that may arise when working closely with organisations in sensitive research.